2011
DOI: 10.4025/actascitechnol.v33i4.9615
|View full text |Cite
|
Sign up to set email alerts
|

Painéis de partículas à base de bagaço de cana e resina de mamona – produção e propriedades

Abstract: Este trabalho apresenta um estudo do potencial de utilização do bagaço de cana-de-açúcar para fabricação de painéis de partículas aglomeradas utilizando resina poliuretana à base de óleo de mamona. A qualidade dos produtos foi avaliada com base nas prescrições do documento normativo NBR 14810 (ABNT, 2006b), com a determinação da densidade, do inchamento, da absorção, do Módulo de Elasticidade (MOE) e Módulo de Ruptura (MOR) na flexão estática. Após análise dos resultados, os painéis avaliados apresentaram dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
28

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 4 publications
2
21
1
28
Order By: Relevance
“…The particleboards treated at 130°C showed a significantly lower TS than those treated at 90 and 110°C (F=6.47, P < 0.05), indicating that the compression temperature was a predominant variable in curing the adhesive. However, the mean TS values obtained for all the particleboards were lower than those reported by Sartori et al 38 and Fiorelli et al 29 . Tables 2 and 3 list the results of the mechanical tests of static bending strength (MOR and MOE), perpendicular tensile strength (IB) and screw pullout (SP) and their respective coefficients of variation.…”
Section: Physical Characterization Of the Particleboardscontrasting
confidence: 51%
See 1 more Smart Citation
“…The particleboards treated at 130°C showed a significantly lower TS than those treated at 90 and 110°C (F=6.47, P < 0.05), indicating that the compression temperature was a predominant variable in curing the adhesive. However, the mean TS values obtained for all the particleboards were lower than those reported by Sartori et al 38 and Fiorelli et al 29 . Tables 2 and 3 list the results of the mechanical tests of static bending strength (MOR and MOE), perpendicular tensile strength (IB) and screw pullout (SP) and their respective coefficients of variation.…”
Section: Physical Characterization Of the Particleboardscontrasting
confidence: 51%
“…In another study, Fiorelli et al 29 investigated the production and properties of particleboards made of sugarcane bagasse and castor oil mono-component and bi-component resin. The characterized materials, which presented an average density of 0.93 g⋅cm -3 , can be classified as high density material recommended for industrial use, showing that castor oil based resin was efficient as a polymer matrix for the production of composite boards made of sugarcane bagasse.…”
Section: Dias and Lahrmentioning
confidence: 99%
“…However, the literature indicates some strategies that can reduce water absorption and swelling, such as the application of waterproofing agents (adhesives or paraffin) that block the absorption sites (Fiorelli et al, 2011) or the thermal treatment of particles, since Which strengthens the dimensional stability of the composite due to the degradation of the hemicellulose, which releases the compression stress formed during pressing (Carvalho et al, 2015).…”
Section: Physical-mechanical Characterization Of Fabricated Particlebmentioning
confidence: 99%
“…The use of lignocellulosic fibers and cellulose whiskers, in the raw or modified forms, as a mechanical support for devices based on both natural and synthetic polymers has been the target of current and growing investigations aiming at developing inorganic material-based biocomposites (NETO et al, 2007;PINTO et al, 2005). Cellulose fibers, such as whisker (CW) or nanowhisker (CNW), may be modified by different processes (BRINCHI et al, 2013;FIORELLI et al, 2011). Some studies have demonstrated that the chemical treatments reduce fiber impurity, increase the effective fiber surface area, and significantly improve interfacial matrix/fiber adhesion.…”
Section: Introductionmentioning
confidence: 99%